Protocatechuic Acid Alleviates Dextran-Sulfate-Sodium-Induced Ulcerative Colitis in Mice via the Regulation of Intestinal Flora and Ferroptosis - Xuebin Yang; Xin Sun; Feng Zhou; Shuiping Xiao; Lulu Zhong; Shian Hu; Zhe Zhou; Ling Li; Yang Tan (Molecules, 2023)
Protocatechuic acid (PCA) is a natural component with multiple biological activities. However, the underlying mechanisms of the effects of PCA on anti-ulcerative colitis (UC) are unclear. A UC mouse model was established by allowing the mice to freely drink a dextran sulfate sodium solution. The mice were administered PCA intragastrically for 7 days. Histological pathology, intestinal flora, and ferroptosis regulators were determined in vivo. Additionally, ferroptotic Caco-2 cells were modeled to investigate the role of PCA in ferroptosis. Our results showed that PCA reduced the levels of the disease activity index, inflammatory factors, and histological damage in UC mice. We also found that the regulation of intestinal flora, especially Bacteroidetes, was one of the potential mechanisms underlying the protective effects of PCA anti-UC. Moreover, PCA downregulated the level of ferroptosis in the colon tissue, as evidenced by a reduced iron overload, decreased glutathione depletion, and a lower level of malondialdehyde production compared with the model group. Similar effects of PCA on ferroptosis were observed in Erastin-treated Caco-2 cells. The results obtained using reactive oxygen species assays and the changes in mitochondrial structure observed via scanning electron microscopy also support these results. Our findings suggested that PCA protected against UC by regulating intestinal flora and ferroptosis.